Coping with a MEDLIB-L service outage - BROWN, Christine D; MACCALL, Steven (Bulletin of the Medical Library Association, 2001)
The study assessed the coping strategies of MEDLIB-L subscribers during an unexpected disruption in the list's service. An online survey of MEDLIB-L subscribers was performed following a six-day service outage in August 1999. Respondents' information needs resulted in two distinct coping strategies. Subscribers without a recognized information need or an information need determined to be not pressing coped by waiting out the interruption. Subscribers with pressing information needs turned to alternative methods of resolving these needs. While most respondents missed the list and the assistance that it provided, many did not feel that the outage required significant coping strategies. The outage was viewed as a "minor stressor" and did not require secondary-level assessment of the availability and suitability of alternative resources.